A comparison of Kotler's and Sharp's theories : Are the customer bases of brands different? - Luongová, Karina Trang; Karlíček, Miroslav, 1979-; Koudelka, Jan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
The objective of this thesis is to determine whether brand customer bases differ. All brands aim to grow and acquire more customers, but are they always doing it right? In marketing, there is a debate about whether brands need to differentiate themselves to be successful and grow, or if differentiation is not as crucial a factor for customers when selecting and purchasing a brand. The theoretical section discusses how Philip Kotler and Byron Sharp view this issue, with Sharp often challenging Kotler’s theory in practice. In the practical part of this work, MML–TGI data are analysed, as in Sharp’s examples. An analysis is applied across thirteen FMCG product categories to uncover differences among brand customers in terms of gender, age, and education. The results revealed fewer significant differences but more minor deviations that are not as impactful. In most cases, there are no differences between customer bases.
Vedoucí práce: Miroslav Karlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses